Quantifying the Impacts of Vehicle-Generated Dust : A Comprehensive Approach - Greening, Tony (World Bank, Washington, DC, 2017)
This project can be considered to be an initial process leading to the ultimate objective of identifying and assigning costs associated with the impacts of vehicle-generated dust so that the benefits can be quantified, if these impacts are ameliorated through actions such as the provision of a sealed road surface. The report outlines the background to the project, the results of the review process, describes the need for a comprehensive approach and identifies and provides some provisional estimates the possible impacts of traffic generated dust on road safety, health, agriculture and the environment. The objectives of the project, the achievements made, the problems encountered and the findings to date are described. The report outlines the overall approach that has been undertaken to achieve the stated aims of the project in relation to the available data. The outcomes from discussions with prospective developing country partners are reported together with the results of correspondence and discussions with other professionals. Recommendations and conclusions are made on the work undertaken to date. An outline methodology and terms of reference are provided for a follow-up study.